Aelred doktorem przyjaźni chrześcijańskiej - Ryszard Groń (Wrocławski Przegląd Teologiczny)
The paper is designed to explain the title of „Doctor of Christian Friendship” that contemporary theological tradition conferred on Aelred (1110–1167), a Cistercian abbot from the English monastery in Rievaulx. The title, set in tradition of the Church, has a lot in common with the institution of “Doctor of the Church”, an honor officially conferred on eminent saints and scholars of philosophy and theology, who laid the foundation for growth of Christian theology. Aelred, lacking in sufficient erudition and official proclamation on the part of the institutional Church, is called the doctor of friendship more in academic circles, because his theological influence is mostly noted in the teaching on friendship. And indeed, his teaching, despite its Ciceronian-Augustine form, is systematic, coherent and original and therefore deserves him the title of master philosophy and theology of friendship. Translated